A starch-bridging strategy for achieving multi-performance synergy of solid-state ionic elastomers toward multimodal sensing - Huidong Liu; Jiang Liu; Meilin Zhang; Zehong Jin; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Carbohydrate Polymers, 2026)

Salivary Mycobiome and Metabolomic Profiles in HIV-Infected Men Who Have Sex with Men: An Exploratory Study - Lu Lin; Miao Zhang; Meilin Guan; Si Chen; Yan Wang; Jie Cao; Wei An; Ying Guo (Current Microbiology, 2026)

The processes and impacts of drought-induced extreme glacier mass loss on the south‐central Tibetan Plateau - Derui Luo; Daijiao Lin; Yichan Xu; Meilin Zhu; Fei Zhu; Huabiao Zhao; Yang Xiang (Journal of Hydrology, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Cigarette smoking combines with genetic variants to regulate FOXN3 and associate with bladder cancer risk - Yiwen Zheng; Youhan Wu; Jinyue Zhang; Chenfei Zhao; Tianqin Wang; Qunbo Wang; Qiang Lv; Chao Qin; Lin Yuan; Haiyan Chu; Mulong Du; Meilin Wang; et al. (Archives of Toxicology, 2026)

Measuring airport catchment areas via the Huff gravity model calibrated with mobile location data—Evidence from the Yangtze River Delta region - Yao Wang; Liushan Lin; Xiaodong Meng; Meilin Zhu; Changcheng Kan (Journal of Transport Geography, 2026)

Water vapor-mediated cellulose skeleton enhances liquid-free ion-conductive elastomers for flexible electronics - Zongming Lv; Hongping Li; Meilin Zhang; Yuanyuan Lao; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Chemical Engineering Journal, 2026)

Stable soil aggregates and complex microbial networks enhances soil quality in saline-alkali agroecosystem - Bangyan Zhang; Jinmin Wu; Rui Bu; Xiaoli Zhang; Xiaolong Bai; Lei Li; Meilin Lin; Yifei Zhang; Xing Xu; Bin Wang (Plant and Soil, 2026)

Mid-late Holocene environmental change and social resilience in Central Plains of China: Evidence from Sha-Ying Rivers floodplain - Wei Li; YiHsien Lin; Linjing Liu; Xiaochen Pei; Ligang Zhou; Yanpeng Cao; Chen Liu; Hui Wang; Peng Lu; Yijie Zhuang; Meilin Guo; Fawei Liang; et al. (Quaternary Science Reviews, 2026)

Microbial community structure and functional diversity affected by soil depth, tidal levels, and stand ages in restored Sonneratia apetala mangroves - Wenxiao Su; Zeyu Lin; Yiyuan Lin; Genmei Lin; Long Wei; Meilin Wu; Jianxiang Feng (Estuarine, Coastal and Shelf Science, 2025)

Microwave-mediated fibrous blended gels of crab meat and surimi: Fibrous protein production method in the perspective of structural remodeling - Qiang Li; Hongyi Wang; Jianfeng Lu; Mengru Yang; Meilin Zhang; Lin Lin; Chenghui Wang (Innovative Food Science & Emerging Technologies, 2025)

Designing a reengineered probiotic yeast to spontaneously degrade residual antibiotics in gut during antimicrobial therapy - Qian He; Zhuoyu Lin; Xiaojing Zhang; Meilin Qin; Yu Huang; Xiaoping Liao; Yahong Liu; Hao Ren; Jian Sun (Journal of Cleaner Production, 2024)

An insight into effect of soil salinity on vegetation dynamics in the exposed seafloor of the Aral Sea - Zihao Duan; Xiaolei Wang; Lin Sun; Meilin Zhou; Yi Luo (Science of The Total Environment, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Enocyanin alleviates experimental colitis and restores gut microbiota homeostasis as functional foods - Cang Li; Yu Huang; Meilin Qin; Qian He; Zhuoyu Lin; Xiaojing Zhang; Hao Ren; Dan Xu; Xiaoping Liao; Yahong Liu; Jian Sun (Food Bioscience, 2024)

Effects of combined polystyrene nanoplastics and ibuprofen on the activated sludge processes: Short-term exposure in pure cultures versus long-term stress in mixed communities - Daying Chen; Mengxiao Li; Yang Li; Sha Long; Ximing Sun; Hongzhi Geng; Meilin Yin; Yongkui Yang; Lin Zhao (Journal of Water Process Engineering, 2024)

Fabrication of a novel gas diffusion electrode (g-C3N4/CB/PTFE-GF) for electro-Fenton treatment of amaranth dye - Daying Chen; Hongzhi Geng; Pengfei Hou; Yihan Li; Sha Long; Meilin Yin; Xiaohui Wang; Lin Zhao (Journal of Water Process Engineering, 2023)

Start-up mechanism of simultaneous nitrification-endogenous denitrification process for treatment of low C/N wastewater: Insights into reactor performance and microbial community dynamics - Daying Chen; Yongkui Yang; Hongzhi Geng; Danning Chen; Zhi Qiao; Meilin Yin; Xiaohui Wang; Lin Zhao (Journal of Cleaner Production, 2023)

Deterministic and Probabilistic Health Risk Assessment of Toxic Metals in the Daily Diets of Residents in Industrial Regions of Northern Ningxia, China - Yan Wang; Deyan Cao; Jiaqi Qin; Siyuan Zhao; Jianzai Lin; Xi Zhang; Junji Wang; Meilin Zhu (Biological Trace Element Research, 2023)
This study was designed to investigate the toxic metal (aluminum (Al), arsenic (As), chromium (Cr), cadmium (Cd), copper (Cu), nickel (Ni), lead (Pb), and zinc (Zn)) concentrations in drinking water and different foodstuffs meat (pork, beef, and mutton), cereals (rice, flour, corn, millet), beans (cowpeas, tofu), potatoes (potato, sweet potato), solanaceous fruits (pepper, eggplant, bitter gourd, cucumber), vegetables (cabbage, cauliflower, spinach), and fruits (apples, watermelons, pears, grapes)) and then estimate the potential health risks of toxic metal consumption to local residents in industrial regions of northern Ningxia, China. As in drinking water, Cr in meat, Pb in cereals, Pb in beans, As and Pb in potatoes, Pb in solanaceous fruits, Cr and Ni in vegetables, and Ni and Pb in fruits were the most contaminated heavy metals in the corresponding food with over-standard rates of 16.7%, 12.5%, 5.1%, 60%, 50%, 50%, 38.2%, 44.4%, 44.4%, 31.8%, and 31.8%, respectively. The results of the deterministic assessment of health risks showed that the total noncarcinogenic risk value of dietary intake of toxic metals by the local population was 5.6106, indicating that toxic metals pose a high noncarcinogenic risk. The order of the non-carcinogenic risk is HI cereal (1.2104) > HI solanaceous fruit (0.9134) > HI Vegetables (0.8726) > HI Fruit (0.8170) > HI Meat (0.7269) > HI Drinking water (0.6139) > HI Beans (0.2991) > HI Potatoes (0.1573). The total carcinogenic health risk from exposure to toxic metals through dietary intake was 9.98 × 10 −4 , indicating that the total cancer risk value of residents is beyond the acceptable range (10 −4 ) under the current daily dietary exposure and implies a high risk of cancer. The order of the carcinogenic risk is R Drinking water (2.34 × 10 −4 ) > R Meat (2.11 × 10 −4 ) > R solanaceous fruit (1.89 × 10 −4 ) > R Fruit (1.88 × 10 −4 ) > R cereal (1.36 × 10 −4 ) > R Potatoes (2.44 × 10 −5 ) > R Vegetables (1.51 × 10 −5 ) > R Beans (0). The probabilistic assessment results showed that 98.83% of the population is exposed to severe noncarcinogenic risk and 87.02% is exposed to unacceptable carcinogenic risk. The sensitivity analysis showed that drinking water, local cereals, vegetables, and fruits were the major contributors to health risks. Our results indicated that the daily dietary exposure of residents in industrial regions of northern Ningxia poses a serious threat to human health, and it is suggested that relevant departments should strengthen monitoring and control of the current situation of toxic metal pollution in the environment and continue to pay attention and take measures to reduce the exposure of toxic metals in the diets of residents in this area. Graphical Abstract

Editorial: Macroecology of coastal zones under global changes - Meilin Wu; Hui Zhao; Qiuying Han; Lin Hui; Vetrimurugan Elumalai; Luzhen Chen; Keerthi Sri Senarathna Atapaththu (Frontiers in Marine Science, 2023)

Fabrication of a SnO2–Sb electrode with TiO2 nanotube array as the middle layer for efficient electrochemical oxidation of amaranth dye - Daying Chen; Lin Zhao; Danning Chen; Pengfei Hou; Jiashu Liu; Chuanbin Wang; Moses Akintayo Aborisade; Meilin Yin; Yongkui Yang (Chemosphere, 2023)

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

Spatiotemporal characteristics of summer hypoxia in Mirs Bay and adjacent coastal waters, South China - Lin Luo; Meilin Wu (Journal of Oceanology and Limnology, 2023)

New insight into the combined effects of ibuprofen and Cu (II) on activated sludge system: System performance, community structure, microbial interaction network - Daying Chen; Minglu Zhang; Yanwen Qin; Zhimin Wang; Meilin Yin; Minghan Zhu; Lin Zhao; Xiaohui Wang (Journal of Environmental Chemical Engineering, 2023)

Editorial: Coastal environmental and ecological data analysis - Meilin Wu; Yu-Pin Lin; Ana Carolina Ruiz-Fernández; Biraja Kumar Sahu (Frontiers in Marine Science, 2023)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

The effect of future reduction in aerosol emissions on climate extremes in China - Zhili Wang; Lei Lin; Meilin Yang; Yangyang Xu (Climate Dynamics, 2016)

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

Short-term effects of multiple ozone metrics on daily mortality in a megacity of China - Tiantian Li; Meilin Yan; Wenjun Ma; Jie Ban; Tao Liu; Hualiang Lin; Zhaorong Liu (Environmental Science and Pollution Research, 2015)

Global and local brain network reorganization in attention-deficit/hyperactivity disorder - Pan Lin; Jubao Sun; Gang Yu; Ying Wu; Yong Yang; Meilin Liang; Xin Liu (Brain Imaging and Behavior, 2014)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

The polymorphisms of IL-4, IL-4R and IL-13 genes and bladder cancer risk in a Chinese population: a case–control study - Haiyan Chu; Lan Ma; Meilin Wang; Danni Shi; Chao Qin; Lin Yuan; Changjun Yin; Zhengdong Zhang (Molecular Biology Reports, 2012)

High incidence of JC viruria in JC-seropositive older individuals - Han Chang; Meilin Wang; Rong-Tai Tsai; Hui-Sheng Lin; Jin-Shue Huan; Wen-Chuang Wang; Deching Chang (Journal of NeuroVirology, 2002)